Researching the home using architectural and social science methods. Issue 2 (August 2018) - Lewis, Camilla; May, Vanessa; Hicks, Stephen; Costa Santos, Sandra; Bertolino, Nadia
This article explores the possibilities of using innovative, interdisciplinary methods for understanding home-making. Drawing on a study of Claremont Court (1959–1962), a post-war social housing scheme designed by Sir Basil Spence in Edinburgh, we discuss the methodological potentials of combining architectural and social science methods to study the home. Claremont Court was built in the post-war era as part of Scotland's social housing drive. It was designed following the principles of 'cross-class' living in order to foster a sense of community. In subsequent years, inhabitants of the court have adapted their dwellings in numerous ways and the population of the court has changed dramatically. But, while meanings of home and understandings of the division between public and private have been reconfigured, the spatial layouts of the dwellings continue to shape residents' sense of home. To explore how residents make home at Claremont Court, we use 'facet methodology', which opens up new ways of thinking about the research process through a 'playful' approach to epistemology. In doing so, we develop an innovative approach which combines architectural methods (including survey drawings and visual mappings of both dwellings and communal areas) with social science methods (including 'traditional' interviews and walk-along interviews). To conclude, we discuss the possibility of widening the scope of qualitative research by bringing architectural and social science methods into dialogue through visual methods, in order to attend to spatial and material aspects of the home. We argue that our novel cross-disciplinary approach broadens understandings of home, by bringing attention to the unspoken dimensions of physical space, embodied elements of home and what people said about their homes, all of which are central to home-making.